Optimalisasi Peran Lembaga Pemasyarakatan Perempuan Kelas IIA dalam Mendukung Tujuan Pemidanaan dalam Sistem Peradilan Pidana - Zakaria, Zakaria (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Women's correctional institutions hold a strategic role in achieving penal objectives, particularly in the rehabilitation and social reintegration of female inmates. This article aims to analyze how the role of Class IIA Women's Correctional Institutions can be optimized to support penal goals such as rehabilitation, resocialization, and recidivism prevention within the criminal justice system. The research uses normative and empirical juridical approaches, with a case study focused on a Class IIA Women’s Prison. The findings reveal several obstacles in optimizing institutional functions, including limited human resources, inadequate rehabilitation facilities, and lack of societal support. Therefore, structural reforms, institutional capacity building, and inter-agency collaboration are essential to ensure that penal goals are not only repressive but also rehabilitative and restorative in nature.